Novel therapeutic strategies in the treatment of triple-negative breast cancer. (July 2017) - Oualla, Karima; El-Zawahry, Heba M.; Arun, Banu; Reuben, James M.; Woodward, Wendy A.; Gamal El-Din, Heba; Lim, Bora; Mellas, Nawfel; Ueno, Naoto T.; Fouad, Tamer M.
Triple-negative breast cancer (TNBC) is a heterogeneous subtype of breast cancer that is defined by negative estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) status. Treating patients with TNBC remains clinically challenging, as patients are not candidates for endocrine or HER2-directed therapy. As a result, chemotherapy with traditional agents such as anthracyclines and taxanes remains the only available option with moderate success. Recent discoveries have revealed that TNBC is a heterogeneous disease at the clinical, histological and molecular levels. The use of biomarkers to identify distinct subsets of TNBC that derive the greatest benefit from presently approved as well as novel therapeutics has become the main focus of current research. The aim of this review is to explore the clinical and biological complexity of TNBC as well as identify novel therapeutic options that target the various molecular subsets of TNBC.